Health Seeking Behavior Pengobatan Akupuntur Pasien Penyakit Degeneratif Berbasis Health Belief Model Theory - Abdullah, Ikhwan; Diana, Sulis; Anggreni, Dhonna (MAHESA : Malahayati Health Student Journal, 2025)
ABSTRACT Degenerative diseases are currently becoming a global problem, including in Indonesia. The results interviews at 5 patients with degenerative diseases that 3 people (60%) had positive health seeking behavior (HSB) by seeking treatment directly to health workers, combining non-pharmacological acupuncture; 2 people (40%) had HSB negative without seeking treatment to health provider, buying various types of drugs at pharmacies. To determine the HSB of Acupuncture Treatment for Patients with Degenerative Diseases Based on the Theory of the HBM. Observational with a cross sectional, the population were all degenerative patients who came to Balai Kesehatan Tradisional Sehat Harmoni Indonesia Malang City with an estimated 3-month of 145 people, sample were 107 people, consecutive sampling, questionnaire instruments, patient medical records, observation sheets, multiple logistic regression data analysis with SPSS. Socioeconomic, knowledge level have an indirect effect on the HSB pattern. through threat beliefs, benefit beliefs; the level of knowledge affects threat beliefs 4.131 times and socioeconomic 0.236 times; knowledge level affected 2,641 times of benefit beliefs, the benefit beliefs affected the compliance of the HSB pattern of acupuncture 8,118 times, and the self-efficacy 7,033 times. Cues to action in the form of professionalism of therapists, where health services have a good image 3,132 times the opportunity to influence HSB compliance with acupuncture treatment. Socioeconomic status and knowledge level only affects threat and benefit beliefs, and health seeking behavior patterns are only influenced by benefit beliefs, self-efficacy and cues to action. Keywords: Health Belief Model Theory, Health Seeking Behavior, Acupuncture, Degenerative Disease  ABSTRAK Penyakit degeneratif saat ini sedang menjadi permasalahan global termasuk di Indonesia. Hasil wawancara 5 orang pasien penderita penyakit degeneratif bahwa 3 orang (60%) memiliki health seeking behavior (HSB) positif dengan mencari pengobatan langsung ke petugas kesehatan, mengkombinasi non farmakologi akupunktur; 2 orang (40%) memiliki HSB  negatif tanpa melakukan tindakan pencarian pengobatan ke tenaga medis, membeli berbagai jenis obat di apotik.  Mengetahui Health Seeking Behavior Pengobatan Akupunktur Pasien Penyakit Degeneratif Berbasis Teori Health Belief Model. Observasional dengan pendekatan cross sectional, populasi seluruh pasien degeneratif yang datang ke Balai Kesehatan Tradisional Sehat Harmoni Indonesia Kota Malang dengan estimasi pasien 3 bulan yaitu 145 orang, sampel 107 orang, teknik consecutive sampling, instrument kuesioner, rekam medis pasien, lembar observasi, analisis data regresi logistik berganda dengan SPSS. Status sosial ekonomi dan tingkat pengetahuan berpengaruh secara tidak langsung terhadap pola HSB. melalui keyakinan ancaman dan keyakinan manfaat, Tingkat pengetahuan mempengaruhi keyakinan ancaman 4,131 kali dan status sosial ekonomi 0,236 kali; tingkat pengetahuan mempengaruhi 2,641 kali keyakinan manfaat, keyakinan manfaat responden mempengaruhi kepatuhan pola HSBakupuntur 8,118 kali, self efficacy sebesar 7,033 kali. Cues to action berupa professionalisme petugas terapis, tempat pelayanan kesehatan memiliki image yang baik dengan peluang sebanyak 3,132 kali mempengaruhi kepatuhan HSB pengobatan akupunktur pasien penyakit degeneratif. Status sosial ekonomi dan tingkat pengetahuan hanya mempengaruhi keyakinan ancaman dan manfaat, dan pola health seeking behavior hanya dipengaruhi oleh keyakinan manfaat, self efficacy dan cues to action. Kata Kunci: Health Belief Model Theory, Health Seeking Behavior, Akupuntur, Penyakit Degeneratif